The relationship between hepatitis B virus serum DNA, RNA and quantitative hepatitis B surface antigen, and the predictive value for mother‐to‐child transmission: an observational cohort study. (21st September 2021) - Wang, C; Pan, Y‐C; Jia, Z‐F; Chi, X‐M; Wang, Y‐Q; Yang, N; Wu, Y‐H; Niu, J‐Q; Jiang, J
Abstract : Objective: To explore the relationships between hepatitis B virus (HBV) DNA, HBV RNA and hepatitis B surface antigen (HBsAg) and to evaluate their predictive value for mother‐to‐child transmission of HBV. Design: An observational cohort study. Setting: First Hospital of Jilin University. Population: HBsAg‐positive and hepatitis B e antigen (HBeAg) ‐positive pregnant women were recruited. Methods: Blood samples were collected from mothers before delivery, and HBV infection of infants was evaluated at 7 months of age. Results: Overall, 268 mothers and 271 infants were enrolled. HBV DNA and HBsAg levels were correlated ( rs = 0.699; P < 0.001), and HBV DNA ( rs = 0.500; P < 0.001) and HBsAg ( rs = 0.372; P < 0.001) were both correlated with HBV RNA. The areas under the curve for HBV DNA, HBsAg and HBV RNA for prediction of infection were 0.69 (95% CI 0.57–0.82), 0.63 (95% CI 0.51–0.76) and 0.65 (95% CI 0.52–0.78), respectively. Higher HBV DNA (odds ratio [OR] 4.77, 95% CI 1.44–15.86), higher HBsAg (OR 4.13, 95% CI 1.12–15.25) and higher HBV RNA (OR 3.19, 95% CI 1.09–9.32) were risk factors for HBV infection. Analysis of the HBV DNA‐RNA‐HBsAg Score revealed that it was an independent predictive factor for mother‐to‐child transmission (the OR of Score 3 was 8.81, 95% CI 2.79–27.82). Conclusion: HBV DNA, HBV RNA and HBsAg were correlated in HBeAg‐positive pregnant women. HBsAg could be considered as a substitute marker of HBV DNA for HBeAg‐positive pregnant women in low‐income regions. We should pay special attention to pregnant women with high levels of all three markers. Tweetable abstract: HBsAg could be considered as a substitute marker of HBV DNA for HBeAg‐positive pregnant women in low‐income regions. Special attention should be given to pregnant women with high levels of all three markers (HBV DNA, HBV RNA and HBsAg). Tweetable abstract: HBsAg could be considered as a substitute marker of HBV DNA for HBeAg‐positive pregnant women in low‐income regions. Special attention should be given to pregnant women with high levels of all three markers (HBV DNA, HBV RNA and HBsAg).